The politics of inclusive development : interrogating the evidence - Hickey, Samuel, 1972-; Sen, Kunal, 1961-; Bukenya, Badru (Oxford : Oxford University Press, 2015)
This collection brings together internationally-renowned experts to offer a comprehensive review of how politics shapes inclusive development in the global south. Each aspect of development is covered: social, economic, environmental and cultural, with each substantive chapter offering a systematic review of the evidence in the relevant field.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 17, 2014).
Keywords: Economic development; Developing countries -- Economic integration